Perubahan Fonem pada Penderita Gangguan Berbahasa Bibir Sumbing - Dicky Irawan, Windo; Fuad, Muhammad; Siti, Siti Ani Nur’aini; Erinda , Erinda Adistina; Via, Via Sapitri; Firliyana, Firliyana; Miranda , Miranda Santika (Edukasi Lingua Sastra, 2024)
Cleft lip and palate sufferers often experience language disorders that can affect aspects of their communication. An in-depth understanding of language disorders in this age group is important to provide appropriate interventions and improve their quality of life. This study identified and analyzed language disorders in cleft lip and palate sufferers at the age of 23 years. This study uses a qualitative method. Data was collected by searching for data sources on YouTube, listening intensively and transcribing into written form, marking and noting things related to phoneme changes (dyslalia). The data analysis technique in this study is to classify data according to language disorders in cleft lip and palate sufferers, then analyzed in relation to language disorders with phoneme changes (dyslalia). The results of the research found changes, omissions and unclear pronunciation of phonemes (dyslalia) in several words spoken by cleft lip and palate sufferers.